2019
DOI: 10.1111/bjop.12382
|View full text |Cite
|
Sign up to set email alerts
|

Too exhausted to go to bed: Implicit theories about willpower and stress predict bedtime procrastination

Abstract: While most people are aware of the importance of sleep for their health, well-being, and performance, bedtime procrastination is a pervasive phenomenon that can be conceptualized as a case of self-control failure (Kroese et al., Frontiers in Psychology, 5, 2014, 1). Two daily diary studies (N 1 = 185, N 2 = 137) investigated beliefs about willpower and stress as interactive predictors of bedtime procrastination. Beliefs about willpower capture whether people think of their willpower as limited resource that ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…The current study found that adolescents, who need a good sleep hygiene for their normative development, are sleeping two hours less per night than the recommended number of hours. This finding, despite worrying, is consistent with previous literature [62,63]. Amidst this scenario, the purpose of this paper was to explore the possibility that sleep insufficiency may be due to procrastination of sleep.…”
Section: Discussionsupporting
confidence: 87%
“…The current study found that adolescents, who need a good sleep hygiene for their normative development, are sleeping two hours less per night than the recommended number of hours. This finding, despite worrying, is consistent with previous literature [62,63]. Amidst this scenario, the purpose of this paper was to explore the possibility that sleep insufficiency may be due to procrastination of sleep.…”
Section: Discussionsupporting
confidence: 87%
“…The small interaction found instead (Figure 1), unlike the original findings, might be explained via a hierarchical semantic network, where lower-level concepts activate higher-level concepts more readily than higher-level concepts activate lower-level concepts (Anderson, 1983;Collins & Loftus, 1975)-for example, a lower-level concept "poodle" activates the higher-level concept "dog" more than the reverse. Temptation-related concepts, like procrastination and distraction, do not only apply to academic-goals, but also are relevant in other contexts (e.g., one can procrastinate instead of exercising or going to sleep; Bernecker & Job, 2020;Brown, 2019). Distraction-related temptations may thus reflect a higher-level concept, with more disparate connections to multiple lower-level concepts (academics, exercise, and sleep).…”
Section: Discussionmentioning
confidence: 99%
“…Why are limited willpower theories associated with more fatigue overall, even in the morning? Potentially, students with more limited willpower theorists may still be feeling depletion-like effects from their efforts during the previous day (Bernecker & Job, 2015b) or may have procrastinated going to bed the night earlier, resulting in having had less sleep (Bernecker & Job, 2020). Subjective reports of fatigue might conflate feelings of sleepiness with feelings of mental fatigue.…”
Section: Possible Mechanisms Of Willpower Theoriesmentioning
confidence: 99%